URGENSI PEMISAHAN KEWENANGAN MENGADILI PERSELISIHAN HASIL PEMILIHAN UMUM SERENTAK - Dewi Cahyandari; Ahmad Siboy; Sudarsono Sudarsono (Arena Hukum, 2020)
AbstractProblems arises in the implementation of elections between the election of the President / Vice President who are no longer held separately such as previous Elections. The technical implications are related to the ability of the Constitutional Court to adjudicate disputes over the legislative and presidential elections which are certainly unbalanced with the number of justices and the limited time. This study aims to map the problems experienced by the Constitutional Court in adjudicating disputes over simultaneous election results. The research method used is normative legal research using conceptual, legislation, history and case approach. The results shows that a separation of authority is needed between the disputes over the results of the presidential / vice presidential election with disputes over the results of the DPR, DPD and DPRD elections. The separation is needed to ensure that the election dispute resolution process does not accumulate in one judicial institution and results in a decision which passes the time limit given. With the separation of authority in adjudicating disputes over the results of the presidential election and legislative elections, the Constitutional Court will only focus on adjudicating cases of outcome disputes and other institutions will also focus on prosecuting thousands of legislative electoral disputes.Â AbstrakTerdapat permasalahan dalam penyelenggaraan pemilihan antara pemilihan Presiden/wakil Presiden yang tidak lagi digelar terpisah. Implikasi teknis berkaitan dengan kemampuan MK dalam mengadili perselisihan pemilu legislatif dan Pilpres yang tentu tidak berimbang dengan jumlah hakim konstitusi dan limitasi waktu yang dimiliki. Penelitian ini bertujuan untuk memetakan problematika yang dialami oleh MK dalam mengadili perselisihan hasil pemilu serentak. Metode penelitian yang digunakan adalah penelitian hukum normatif dengan pendekatan konsep, peraturan perundang-undangan, sejarah dan kasus. Hasilnya, diperlukan pemisahan kewenangan mengadili antara perselisihan hasil pemilihan umum Presiden/wakil Presiden dengan perselisihan hasil pemilihan umum DPR, DPD, dan DPRD demi menjamin proses penyelesaian perselisihan hasil pemilihan yang tidak menumpuk disatu lembaga peradilan dan berakibat pada putusan yang melewati batas waktu yang diberikan. Pemisahan ini akan membuat Mahkamah Konstitusi hanya fokus mengadili perkara perselisihan hasil saja dan lembaga lain juga fokus mengadili perselisihan Pileg yang jumlahnya ribuan.Â